DOE-MARCOS: A NEW APPROACH TO MULTI-CRITERIA DECISION MAKING - Duc Trung, Do; Hong Son, Nguyen; Trung Hieu, Tran; Thi Nhu Uyen, Vo (Journal of Applied Engineering Science, 2022)
Choosing the best among the available alternatives seems to be expected in all fields. As each alternative is considered by multiple criteria, the selection of the best alternative must take into account all of those criteria. MCDMs are methods that have been widely used to solve problems of this type. However, if only a certain MCDM is applied, the ranking of alternatives must be done from the beginning as adding/removing one or more alternatives from the option list. This paper presents a probably new approach to deal with this situation. DOE method was used in combination with the MARCOS method to build a relationship between the scores of the options and the criteria. This mix is called DOE-MARCOS. Based on this, the calculation of the scores of the alternatives may be faster and less complicated than only using the MCDM. A simple example was made to evaluate the effectiveness of the proposed method when an alternative was added to the list. Two other examples were also conducted to assess the performance of the proposed method (DOE-MARCOS) in ranking cutting tools. The results of ranking options using the DOE-MARCOS are compared with other methods. Sensitivity analysis in each example under different scenarios was also carried out. Its results show that the proposed method is highly effective for multi-criteria decision making.